Research on Tripod Gait of Bionic Hexapod Robot - LIU Ming-dan; LV Xiao-rong; Qi Xiang-jun; Wei Jiang-shu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Based on the bionic theory and the analyzed of movement mechanism for six-legged insect, the principle of tripod gait movement for walking robot was analyzed in this paper, and basic parameters and the principle of relative movement theory on gait research were discussed. Then the hexapod walking robot was assembled by using the component of Fischertechnik. With the characters of simple connective structure, unique design, this robot can walk forward and backward and can avoid mini-barrier. The experiment showed that this robot has good mobility and stability. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3898